Chemically standardised extract of Withania somnifera (Ashwagandha) inhibits tumour growth, promotes apoptosis and cell cycle arrest - Subasini Uthirapathy; Javed Ahamad
Withania somnifera Dunal (Family: Solanaceae), also known as ashwagandha, is indigenous to Asia and Africa. It is also known as "Indian Ginseng." It has been used for thousands of years in ancient Indian Ayurvedic medicine to reduce stress and pain, increase energy, improve nutrition, and treat various health conditions. The present study aims to determine the chemopreventive potential of a chemically standardised extract of W. somnifera against lung cancer (A549) and breast cancer (MCF-7) cell lines. The anticancer activity of W. somnifera was determined against lung and breast cancer using A549 and MCF-7 cell lines, respectively, in different anticancer models, and the chemical constituent was determined by the GC-MS method. After being treated for 48 hours in MTT assay, W. somnifera successfully reduced the viability of the MCF-7 cell line with an IC50 value of 41.83 (So(Bg/mL in a dose-dependent manner. W. somnifera extract treatment reduced cyclin D1 and E2 expression in A549 cell lines. It was correlated to cell cycle arrest in the G0/G1 phase. Additionally, it decreased nuclear factor gb(B-translocation, a pro-survival signal. In the human lung cancer cell line (A459), the anticancer activity was evaluated by Cas 3 gene expression investigation by RT-PCR. The existence of fatty acids in higher concentrations was revealed by GC-MS analysis of the methanolic fraction from the 70% ethanolic extract of W. somnifera, which produced 28 compounds. Given its apoptogenic and antiproliferative qualities, the observations point to the chemopreventive potential of W. somnifera extract. Additional research is required to investigate these effects in in vivo models.s